2012
DOI: 10.1029/2012pa002337
|View full text |Cite
|
Sign up to set email alerts
|

Deglacial variability of Antarctic Intermediate Water penetration into the North Atlantic from authigenic neodymium isotope ratios

Abstract: Understanding intermediate water circulation across the last deglacial is critical in assessing the role of oceanic heat transport associated with Atlantic Meridional Overturning Circulation variability across abrupt climate events. However, the links between intermediate water circulation and abrupt climate events such as the Younger Dryas (YD) and Heinrich Event 1 (H1) are still poorly constrained. Here, we reconstruct changes in Antarctic Intermediate Water (AAIW) circulation in the subtropical North Atlant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
51
0
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 67 publications
(110 reference statements)
4
51
0
2
Order By: Relevance
“…The last deglaciation presents an ideal target to test our understanding of the relation between AAIW and AMOC. Some previous observational studies of the last deglaciation suggested that the northward penetration of AAIW in the tropical Atlantic should be positively correlated with the AMOC strength (Came et al, ; Huang et al, ; Xie et al, ). This positive correlation seems to be consistent with the notion that AAIW, as part of the North Brazil Current (NBC), contributes to the return branch of North Atlantic Deep Water (NADW) (Lumpkin & Speer, ; Rintoul, ; Schmitz & McCartney, ; Zhang et al, ).…”
Section: Introductionmentioning
confidence: 98%
“…The last deglaciation presents an ideal target to test our understanding of the relation between AAIW and AMOC. Some previous observational studies of the last deglaciation suggested that the northward penetration of AAIW in the tropical Atlantic should be positively correlated with the AMOC strength (Came et al, ; Huang et al, ; Xie et al, ). This positive correlation seems to be consistent with the notion that AAIW, as part of the North Brazil Current (NBC), contributes to the return branch of North Atlantic Deep Water (NADW) (Lumpkin & Speer, ; Rintoul, ; Schmitz & McCartney, ; Zhang et al, ).…”
Section: Introductionmentioning
confidence: 98%
“…DISCUSSION 61 tually weaker during those periods Xie et al, 2012). Our results, therefore, seem to agree with the second hypothesis.…”
Section: Discussionsupporting
confidence: 82%
“…It is believed that the climate swings that followed the LGM were frequently accompanied by changes in the ocean circulation (e.g., Broecker, 1994;McManus et al, 2004;Praetorius et al, 2008). Proxy records show that during cold periods there were reductions in the AMOC while the warm periods were marked by the AMOC's (Xie et al, 2012). Also, the δ The Atlantic Ocean's deglacial evolution:…”
Section: Deep Ocean Circulation Changes In the Last 21000 Yearsmentioning
confidence: 99%
“…Neodymium isotope evidence points both towards a volumetric increase in AAIW at intermediate depths of the equatorial regions 13,14 but also to a decline in AAIW in the Florida Straits during HS1 (ref. 15). While nutrient proxies cannot determine the origins of the water, they do indicate that the mid-depths of the South Atlantic were more enriched in Si(OH) 4 relative to other nutrients during HS1 than they are today 16,17 , suggestive of a northwards advance of AAIW into the North Atlantic during HS1 (ref.…”
mentioning
confidence: 99%